Human Extrafollicular CD4+ Th Cells Help Memory B Cells Produce Igs - Kim, Sang Taek; Choi, Jin-Young; Lainez, Begona; Schulz, Vincent P; Karas, David E; Baum, Eric D; Setlur, Jennifer; Gallagher, Patrick G; Craft, Joe (The Journal of immunology (1950), 2018)
Follicular helper T (Tfh) cells are necessary for germinal center B cell maturation during primary immune responses; however, the T cells that promote humoral recall responses via memory B cells are less well defined. In this article, we characterize a human tonsillar CD4+ T cell subset with this function. These cells are similar to Tfh cells in terms of expression of the chemokine receptor CXCR5 and the inhibitory receptor PD-1, IL-21 secretion, and expression of the transcription factor BCL6; however, unlike Tfh cells that are located within the B cell follicle and germinal center, they reside at the border of the T cell zone and the B cell follicle in proximity to memory B cells, a position dictated by their unique chemokine receptor expression. They promote memory B cells to produce Abs via CD40L, IL-10, and IL-21. Our results reveal a unique extrafollicular CD4+ T cell subset in human tonsils, which specialize in promoting T cell–dependent humoral recall responses.